Claudins and mineral metabolism. Issue 4 (July 2016) - Hou, Jianghui
Abstract : Purpose of review: The tight junction conductance made of the claudin-based paracellular channel is important in the regulation of calcium and magnesium reabsorption in the kidney. This review describes recent findings of the structure, the function, and the physiologic regulation of claudin-14, claudin-16, and claudin-19 channels that through protein interactions confer calcium and magnesium permeability to the tight junction. Recent findings: Mutations in two tight junction genes – claudin-16 and claudin-19 – cause the inherited renal disorder familial hypomagnesemia with hypercalciuria and nephrocalcinosis. A recent genome-wide association study has identified claudin-14 as a major risk gene of hypercalciuric nephrolithiasis. The crystal structure of claudin-19 has recently been resolved allowing the reconstruction of a claudin assembly model from cis -dimers made of claudin-16 and claudin-19 interaction. MicroRNAs have been identified as novel regulators of the claudin-14 gene. The microRNA-claudin-14 operon is directly regulated by the Ca 2+ sensing receptor gene in response to hypercalcemia. Summary: The paracellular pathway in the kidney is particularly important for mineral metabolism. Three claudin proteins – claudin-14, claudin-16, and claudin-19 – contribute to the structure and function of this paracellular pathway. Genetic mutations and gene expression changes in these claudins may lead to alteration of the paracellular permeability to calcium and magnesium, ultimately affecting renal mineral metabolism.